Overview of I research day civil engineering and urban planning UCLA 2015 (Gaceta Técnica, 2016)
Through this essay, the events of the First Day of Civil Engineering Research and Urban Planning 2015 UCLA are detailed which was developed during the 15 and 16 of March 2016, in the premises of the school of Civil Engineering, of the Universidad Centroccidental Lisandro Alvarado. Papers Allusive to research related to civil engineering, specifically in the areas of structures, water and wastewater, construction engineering, and applied to engineering education, were presented. With a total of fourteen approved presentations and four lectures given by experts in the different topics addressed
Keywords: research day; School of civil engineering; civil engineering